Assessing the effect of the Expanding Maternal and Neonatal Survival program on improving stabilization and referral for maternal and newborn complications in Indonesia. (27th February 2019) - Pedrana, Alisa; Qomariyah, Siti Nurul; Tholandi, Maya; Wijayanto, Bambang; Gandawidjaja, Trisnawaty; Amelia, Dwirani; Apriatni, Mandri; Sudirman, Sudirman; Zazri, Ali; Sethi, Reena; Emerson, Mark; Ahmed, Saifuddin
Abstract: Objective: To determine if the Expanding Maternal and Neonatal Survival (EMAS) program was associated with improved effectiveness of the referral system in Indonesia to facilitate timely and effective management of complications experienced by women and newborns. Methods: Poisson regression using longitudinal monitoring data was used to assess the impact of the EMAS program on stabilization practices prior to referral. Data from a nonrandomized quasi‐experimental pre‐post evaluation study were used to assess the impact of the EMAS program along the referral pathway using χ 2 analysis. Results: Monitoring data demonstrated improvements in intervention areas for stabilization of pre‐eclampsia/eclampsia (24% vs 61%, incidence rate ratio [IRR] 2.4; 95% confidence interval [CI], 2.3–2.6) and treatment of newborns with suspected severe infection (30% vs 54%, IRR 2.0; 95% CI, 1.6–2.4) prior to referral. The EMAS program was associated with significantly higher levels of communication, advanced notification, back referral, and hospital emergency readiness and staff preparedness compared with the comparison arm. Conclusion: The EMAS program contributed to improvements in the management of obstetric and newborn complications, including communication, transportation, and preparation of pregnant mothers in need of referral and hospital emergency readiness and staff preparedness. Abstract : The Expanding Maternal and Neonatal Survival program contributed to improvements in stabilization of obstetric complications, referral, and hospital emergency readiness.